Haploidentical Hematopoietic Stem Cell Transplantation as Platform for Post-transplant Cellular Therapy - Kongtim, Piyanuch (Biol Blood Marrow Transplant, 2015)
Haploidentical transplantation can extend the opportunity for transplantation to almost all patients who lack an HLA-matched donor. Advances in the field of haploidentical transplantation have led to a marked decrease in treatment-related mortality, allowing investigators to focus on developing rationale pre- and peri-remission therapies aimed at preventing disease relapse post-transplant. Due to widespread availability, low treatment-related mortality and cost, haploidentical donors may become the preferred “alternative” donors for allogeneic hematopoietic stem cell transplantation. One of the major advantages of using a related donor is the possibility to collect or generate additional cellular products from the same immediate available donor, which will not be rejected. Infusion of these cells in the peri-transplant period, derived from the same immune system, is opening the possibility to markedly enhance the anti-tumor effects of the graft and hasten immunologic reconstitution post-transplant.